(untitled) (Bioscience Journal, 2018)
Microbial biomass is an important component in maintaining soil quality and plant productivity. The aim of this paper was to evaluate alterations in microbiological attributes and organic carbon in accordance with seasonal change in different monocultures in the Savanna region of Piauí state. Soil samples were collected in areas of soy, eucalyptus, pasture, and in an area of native savanna, at depths of 0-0.20 m, during the rainy and dry periods. Using these samples microbial biomass carbon (MBC), basal respiration (BR), metabolic quotient (qCO2), microbial quotient (qMIC), and total organic carbon in the soil (TOC) were evaluated. MBC differed significantly between the systems evaluated, with higher values in the soil under native vegetation in the two sampling periods. TOC presented a significant difference between the systems, with higher values in the native savanna and soybean in the rainy period. For the qMIC, the soybean area presented lower values in the two periods compared with the other areas. Basal respiration as well as qCO2 values differed between the systems only in the dry period. The results reveal that the type of vegetation cover, management system, and seasonality influence the behavior of biological properties in the soil.